CERVICAL CANCER: ETIOLOGY, CLINICAL FEATURES, DIAGNOSIS, AND COMPLICATIONS - Khakimov Galib Abdullaevich; Yuldashev Laziz Temurovich (Scholar Express Journals, 2025)
Cervical cancer remains one of the most common malignancies among women worldwide, especially in developing countries. This article provides a comprehensive overview of the etiology, clinical features, diagnostic approaches, and complications of cervical cancer. Particular attention is paid to human papillomavirus (HPV) as the leading etiological factor, as well as the importance of early detection through screening methods such as Pap smear and HPV testing. The study highlights how delays in diagnosis and treatment can lead to severe complications and higher mortality rates.
Keywords: Cervical cancer; HPV; clinical features; diagnosis